Effects of Compensation on Employees’ Performance in Nepalese Commercial Banks - Luitel, Madan Kumar; Humagain, Krishna (Dristikon: A Multidisciplinary Journal, 2025)
This study analyzes the impact of compensation and benefits on employees’ performance in Nepalese commercial Bank. Employee performance is an important driver of organizational success, and compensation plays a pivotal role in motivating employees. The primary objectives of this research were to determine the compensation and benefit factors influencing employee performance, to examine the relationship between these factors and employee performance, and to assess the effect of specific compensation components, such as overtime allowance, promotion, and social security, on performance. The study employed a quantitative research methodology, using a structured questionnaire to collect data from 153 employees of commercial Banks. The collected data were analyzed using descriptive statistics, correlation analysis, and regression analysis. The findings reveal that compensation factors such as salary, overtime allowance, and social security have a significant positive impact on employee performance. Furthermore, career advancement opportunities, particularly promotions, were found to be a key motivator for improving employee performance. The study concludes that a well-designed compensation package that includes both financial and non-financial benefits can significantly enhance employee motivation and performance. Providing clear career advancement opportunities and a comprehensive benefits package can improve employee satisfaction, performance, and overall organizational effectiveness. Based on these findings, the study suggests that commercial bank and similar organizations should review and enhance their compensation structures to ensure they align with employee needs and industry standards.